A novel use of Stereo Baited Remote Underwater Video and Drop-Down Video for biodiversity and marine landscape mapping and prediction. - Natasha L Walker-Milne; Sophie Elliott; Peter J Wright; David M Bailey (PLoS ONE)
To make the best-informed decisions on managing marine resources whilst also restoring biodiversity, the creation and analysis of benthic maps is highly valuable. This study focuses on benthic mapping to study patch - and landscape - level processes affecting epifauna and demersal species using Stereo Baited Remote Underwater Video (SBRUV) and Drop-Down Video (DDV) surveys. Surveys were conducted within the South Arran Marine Protected Area between 2013-2019 and yielded 554 SBRUV data points and 333 DDV data points. These data were processed to determine proportional coverage of substrata and kriged to produce benthic maps. From this it was possible to estimate the patch scale of substrata to gain a more detailed understanding of the marine landscape, composition structure, and epibenthic biodiversity. The resulting validated maps allowed the number of substrata patches and patch characteristics such as area and perimeter-to-area ratio to be calculated to support management and understanding of the value of this seascapes for benthic and demersal biodiversity. Our approach allowed for the identification of areas of higher biodiversity that may assist during mapping of Marine Protected Areas' (MPA) vulnerable features. These methods should provide better information about site condition and ecosystem service provision than existing methods.